Urban and rural differences in the prevalence of sarcopenia and functional limitations in community-dwelling older adults. - Aziz, Jason. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Food and Nutrition Policy and Programs.; Advisor: Roger Fielding.; Committee: Kieran Reid, and John Batsis.; Keywords: Aging, Nutrition, and Epidemiology.